Does Indonesian Fiscal Decentralization Lead to Local-Central Fiscal Dependency? - Anggriawan, Tommy; Susilo, Susilo; Prasetyia , Ferry (Badan Penerbitan Jurnal (BPJ) FIA-UB, 2025)
This research tries to examine the possibility of central local fiscal dependency as the result of fiscal decentralization in Indonesia by revealing the influence of Vertical Fiscal Imbalance (VFI) on the fiscal sustainability at local government budgeting. It applies VFI, GDRP Percapita, Poverty, Human Development Index, and Unemployment Rate as independent variables and Fiscal Sustainability as dependent variables through the fixed effect model (FEM). The result of this research points out that the implementation of a sharing revenue mechanism under fiscal decentralization policy will provide particular beneficial for the region with plenty fiscal resources, however it would be a drawback for the rest region with less potential for fiscal revenue. The primary implication of this phenomenon is the high dependency between local governments especially with limited fiscal revenue potential to the central government transfer. In addition to the result, this research also identifies the possibility of moral hazard at the local government level due to the escalating amount of intergovernmental grants over the years.